Pitch and Duration Pattern Sequence Tests in 7- to 11-Year-Old Children: Results Depend on Response Mode - Balen, Sheila Andreoli; Moore, David R.; Sameshima, Koichi (Journal of the American Academy of Audiology, 2019)
Pitch pattern sequence (PPS) and duration pattern sequence (DPS) tests are frequently used in the assessment of auditory processing disorder. Current recommendations suggest alternate, interchangeable modes for responding to stimuli.The objective of the study is to evaluate the influence of response mode (i.e., humming, pointing, and labeling) and age on PPS and DPS performance of 7- to 11-year-old children.Laboratory-based testing of school children. Cross-sectional comparison of age, with repeated measures of age, test, ear, and response mode.From 452 children recruited, 228 right-handed children (109 girls) aged 7 years to 11 years 11 months (mean age 9 years 4 months) completed at least one test (PPS: 211, DPS: 198), and 181 children completed both tests. Audiology inclusion criteria include normal hearing thresholds (≤15 dB HL at octave frequencies 250–8000 Hz); word recognition in quiet ≥92%; tympanogram peak compensated static acoustic compliance 0.4–1.6 mmhos; and tympanometric peak pressure −100 to +50 daPa, all in both ears. Other inclusion criteria were Portuguese as first language; right handed; no musical training; no related, known, or observed phonological, learning, neurologic, psychiatric, or behavioral disorder; otologic history; and delayed neuropsychomotor or language development.PPS: 30 trials per ear and response condition of three consecutive 500 msec duration intermixed high (1430 Hz) or low (880 Hz) frequency tones presented monaurally at 50 dB HL. The first response condition was humming followed by labeling (naming: high or low). DPS: As per PPS except 1000 Hz tones of intermixed 500 (long) and 250 msec (short) duration. First response was pointing (at a symbolic object) followed by labeling. Trends across age and between tests were assessed using repeated measures generalized linear mixed models. Correlation coefficients were calculated to assess relations among test scores. The two-sided significance level was 0.05.Older children performed better than younger children in all tasks. Humming the tone pattern (PPS humming) produced generally better performance than either articulating the attributes of the tones (labeling) or pointing to objects representing tone duration. PPS humming produced ceiling performance for many children of all ages. For both labeling tasks and DPS pointing, performance was better on the PPS than on the DPS, for stimulation of the right than the left ear, and in boys than girls. Individual performance on the two tasks was highly correlated.Response mode does matter in the PPS and DPS. Results from humming should not be combined with or be a substitute for results obtained from a labeling response. Tasks that rely on labeling a tonal stimulus should be avoided in testing hearing in children or other special populations.
Keywords: auditory processing disorder; children; duration pattern test; pitch pattern test